Redesign Struktur Bangunan Gedung Utama Indonesia Manufacturing Center Berbasis Building Information Modeling 5D - Dinda Rizki Pratiwi; Okta Dewi Saputri; Bambang Setiabudi; Asri Nurdiana (Universitas Diponegoro, 2025)
The development of increasingly sophisticated technology forces evaluation of construction methods with the speedy development in Indonesia. Strengthened by PUPR Ministerial Regulation No. 22 of 2018 which requires the application of BIM in building construction. Therefore, this planning will center on redesign the Indonesia Manufacturing Center Main Building Project based on Building Information Modeling (BIM) which aims to understand and analyze structural work planning, cost estimation and scheduling. The methods used in this planning are planning data from the Indonesia Manufacturing Center Main Building Project, case studies and literature studies from various verified sources. The stages in preparing this Final Project start from load analysis and dimensional planning, followed by structural analysis with SAP 2000 and 3D modeling with Autodesk Revit. Then the volume results from Autodesk Revit are used for planning cost estimates and scheduling using Microsoft Excel and Microsoft Project which are integrated with Autodesk Naviswork. The results of this planning are a Cost Budget Plan including 11% VAT with a total price of IDR 36,656,464.219,89 and schedule with an implementation duration of 23 weeks.